PENGETAHUAN WAWASAN AL-QUR’AN TENTANG KEPEMIMPINAN PADA YAYASAN DARUL ISTIQOMAH HIDAYATULLOHMOMPANG JULU PANYABUNGAN UTARA MANDAILING NATAL - Harahap, Ade Khadijatul; Rahmat, Rahmat (J-MABISYA, 2021)
The occurrence of disputes in choosing and determining leaders during the khulaf?' al-r?syid?n period, and this continued until the Islamic dynasties, was due to differences in conceptions in understanding the criteria for leaders alluded to by the Qur'an. As an initial illustration, the criteria for leadership that are understood in the Shi'a and Sunni communities are different. This research is in the form of library research. In this research, the researcher uses descriptive analysis method, descriptive analysis is a method by collecting data, compiling or classifying, analyzing and interpreting it to examine the criteria of leadership according to the Qur'an a study of maudhu`iy interpretation. The criteria for a leader according to the Qur'an are faith, fairness, trustworthiness, and apostolic personality with strict conditions, namely experienced, able to eradicate falsehood, can be imitated and obeyed, tolerant, siddiq, patient, fathanah, tablg, underlined, physically and mentally healthy, not physically disabled, knowledgeable, have solidarity, and have great influence in society.